Workplace violence against emergency physicians: A cross-sectional study on the role of communication skills - Mehmet Selim Karpınar; Gülden Hakverdi; S. Ayhan Çalışkan (Turkish Journal of Emergency Medicine, 2025)
OBJECTIVES: Workplace violence (WPV) is a critical issue affecting healthcare professionals, posing significant risks to their safety and well-being. This study investigates WPV among emergency physicians in Türkiye, examining the relationship between WPV and physicians’ communication skills. METHODS: A cross-sectional study was conducted from March to June 2023, involving 63 emergency physicians recruited through a convenience sampling method. Participants completed an online survey that included demographic questions, the Turkish version of the Health Professionals Communication Skills Scale (HP-CSS-TR), and self-evaluation items on communication skills. RESULTS: The findings revealed high WPV prevalence, with 85.7% of participants reporting verbal aggression during their residency and 90.5% during their specialty period. Physical violence was reported by 31.7% of participants during residency and 27.0% during their specialty period. Participants’ HP-CSS-TR scores averaged 86.08, indicating relatively high communication skills. No significant relationships were found between HP-CSS-TR scores and demographic characteristics such as gender, age, or years of experience. A moderate positive correlation was observed between participants’ self-evaluations and their HP-CSS-TR scores in the dimensions of empathy and respect, suggesting alignment between perceived and actual communication skills in these areas. Weak correlations were found in informative communication and social skills, highlighting areas for improvement in communication training programs. CONCLUSIONS: This study highlights the critical issue of WPV against emergency physicians and its association with communication skills, emphasizing the complexities of high-stress environments such as emergency departments. It underscores the need for continued research and systemic interventions to enhance workplace safety and the well-being of healthcare professionals.